The Effect Of Back Massage With Lavender Essential Oil Aromatherapy On Reducing Back Pain Intensity In Pregnant Women In The Thirty-Thirty Trimester - Febrianti, Cindy Putri; Wahyuni, Dwi Reza; Syakila, Wafiq (Oshada, 2025)
Back pain is one of the discomforts often felt by pregnant women entering the third trimester. Treatment to reduce pain can use complementary care, one of which is by providing Back Massage. The aim is to determine the effect of Back Massage with lavender essential oil aromatherapy on the scale of back pain in pregnant women. The research method used a quasi-experimental one group pretest-posttest design. The population of this study was all 30 pregnant women, with a total sample of 15 pregnant women in the third trimester who experienced back pain. The results of the study obtained an average pretest of 0.00 and posttest 6.50, this indicates a difference in the pain scale with the results of p-Value = 0.001 <0.05, which means there is an effect of Back Massage with lavender essential oil aromatherapy on reducing back pain in pregnant women in the third trimester. It is hoped that pregnant women who experience back pain can know the treatment using Back Massage therapy with lavender essential oil aromatherapy.